Cysteine cathepsins and extracellular matrix degradation - Fonović, Marko; Turk, Boris (Biochimica et biophysica acta, 2014)
Cysteine cathepsins are normally found in the lysosomes where they are involved in intracellular protein turnover. Their ability to degrade the components of the extracellular matrix in vitro was first reported more than 25years ago. However, cathepsins were for a long time not considered to be among the major players in ECM degradation in vivo. During the last decade it has, however, become evident that abundant secretion of cysteine cathepsins into extracellular milieu is accompanying numerous physiological and disease conditions, enabling the cathepsins to degrade extracellular proteins. In this review we will focus on cysteine cathepsins and their extracellular functions linked with ECM degradation, including regulation of their activity, which is often enhanced by acidification of the extracellular microenvironment, such as found in the bone resorption lacunae or tumor microenvironment. We will further discuss the ECM substrates of cathepsins with a focus on collagen and elastin, including the importance of that for pathologies. Finally, we will overview the current status of cathepsin inhibitors in clinical development for treatment of ECM-linked diseases, in particular osteoporosis. Cysteine cathepsins are among the major proteases involved in ECM remodeling, and their role is not limited to degradation only. Deregulation of their activity is linked with numerous ECM-linked diseases and they are now validated targets in a number of them. Cathepsins S and K are the most attractive targets, especially cathepsin K as a major therapeutic target for osteoporosis with drugs targeting it in advanced clinical trials. Due to their major role in ECM remodeling cysteine cathepsins have emerged as an important group of therapeutic targets for a number of ECM-related diseases, including, osteoporosis, cancer and cardiovascular diseases. This article is part of a Special Issue entitled Matrix-mediated cell behaviour and properties. •Cysteine cathepsins are major proteases involved in ECM remodeling.•The role of cysteine cathepsins in ECM remodeling is not limited to degradation only.•Deregulation of cathepsin activity is linked with numerous ECM-linked diseases.•Cathepsin K is a major therapeutic target for osteoporosis.